2018
DOI: 10.3791/57157
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Inflammatory Human Tissue Equivalents of Gingiva

Abstract: Periodontal diseases (such as gingivitis and periodontitis) are the leading causes of tooth loss in adults. Inflammation in gingiva is the fundamental physiopathology of periodontal diseases. Current experimental models of periodontal diseases have been established in various types of animals. However, the physiopathology of animal models is different from that of humans, making it difficult to analyze cellular and molecular mechanisms and evaluate new medicines for periodontal diseases. Here, we present a det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Since PKC signaling activates inflammatory responses, PMA is often used as a potent inducer of inflammation in animal models [ 38 , 39 ]. In our previous study, we found that 10 ng/mL of PMA could efficiently induce the differentiation of THP-1 cells, as did other researchers [ 40 , 41 , 42 ]. We also discovered that a longer duration of treatment (more than 4 days) with PMA can promote maturation of THP-1 macrophages (data not shown).…”
Section: Discussionsupporting
confidence: 72%
“…Since PKC signaling activates inflammatory responses, PMA is often used as a potent inducer of inflammation in animal models [ 38 , 39 ]. In our previous study, we found that 10 ng/mL of PMA could efficiently induce the differentiation of THP-1 cells, as did other researchers [ 40 , 41 , 42 ]. We also discovered that a longer duration of treatment (more than 4 days) with PMA can promote maturation of THP-1 macrophages (data not shown).…”
Section: Discussionsupporting
confidence: 72%
“…Current studies have suggested that tumor cells regulate the polarization process of macrophages through a variety of mechanisms. To understand the role of prostate cancer exosomes in macrophage polarization, we first induced THP1 cells into macrophages with 10 ng/ml PMA for 72 h [ 20 ], and then these macrophages were treated with IFN-γ (50 ng/mL), IL-4 (25 ng/mL), 2B4-exos (100 μg/ml), and IE8-exos (100 μg/ml) [ 21 ]. After culturing them for 48 h, we observed that, similar to the macrophages induced by IL-4, macrophages treated by 2B4-exos or IE8-exos significantly over-expressed CD206, a molecular marker of the M2 phenotype, IL-10 (M0 vs. 2B4-exo-Mφ, p < 0.0001; M0 vs.1E8-exo-Mφ, p = 0.0004) and TGF-β1 (M0 vs. 2B4-exo-Mφ, p = 0.0001; M0 vs. 1E8-exo-Mφ, p = 0.0004) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…18 Xiao et al punched a hole in a full-thickness OME composed of primary gingival fibroblasts, topped with the HaCaT skin keratinocyte cell line and injected it with LPS-stimulated, PMA-differentiated THP-1 cells to mimic periodontal disease. 20 Bao et al 22 developed a similar periodontal model using HPV E6/7-immortalized gingival fibroblasts, keratinocytes, and MM6 cells to produce an immune model that was then challenged with multispecies bacterial biofilm to mimic subgingival plaque. To date, Holmström et al have developed the most characterized immune-responsive OME.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have generated immune oral gingival models by incorporating primary monocytes, peripheral blood mononuclear cells, or myeloid cancer cell lines (MonoMac-6 [MM6], U937, or THP-1 cells) and by observing changes in inflammatory markers and proteases in response to bacterial LPS, [18][19][20][21] bacterial biofilms, 22 or X-ray treatment. 23 While the use of myeloid cancer cell lines presents fewer technical limitations and reproducibility compared with primary immune cells, there is good evidence that their phenotype and function is markedly altered compared with primary cells, with the often used THP-1 cells shown to express aberrant levels of key macrophage phenotypic markers and thus respond differently to stimuli.…”
Section: Introductionmentioning
confidence: 99%